2023
DOI: 10.1093/jxb/erad210
|View full text |Cite
|
Sign up to set email alerts
|

Resolving intergenotypic Striga resistance in sorghum

Abstract: Genetic underpinnings of host-pathogen interactions in the parasitic plant Striga hermonthica, a root parasitic plant that ravages cereals in sub-Saharan Africa, are unclear. We performed a comparative transcriptome study on five genotypes of sorghum exhibiting diverse resistance responses to S. hermonthica using weighted gene co-expression network analysis (WGCNA). We found that S. hermonthica elicits both basal and effector-triggered immunity – like a bona fide pathogen. Resistance response was genotype spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…This study has sought to analyze the pathogenesis of CLas, despite the ambiguity surrounding its unculturable nature in vitro . In the realm of plant science, WGCNA has proven to be a powerful tool for exploring complex genetic traits and plant responses to various environmental factors ( Mutinda et al., 2023 ). Unveiling these hub genes can lead us to the genetic controls underlying critical physiological traits, stress responses, and adaptation strategies in plants ( Yu et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study has sought to analyze the pathogenesis of CLas, despite the ambiguity surrounding its unculturable nature in vitro . In the realm of plant science, WGCNA has proven to be a powerful tool for exploring complex genetic traits and plant responses to various environmental factors ( Mutinda et al., 2023 ). Unveiling these hub genes can lead us to the genetic controls underlying critical physiological traits, stress responses, and adaptation strategies in plants ( Yu et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Further experimental data confirmed the role of DcWRKY3/4 in regulating the metabolic pathway of flavonoids ( Li et al., 2024 ). In the complex interplay between sorghum and the parasitic plant Striga hermonthica , the use of WGCNA facilitated the identification of several key genes playing a role in resistance response ( Mutinda et al., 2023 ). During Sporisorium scitamineum infection, the transcriptomic profiling of sugarcane pinpointed 38 pivotal genes by WGCNA, incorporating those encoding chitinase, glutathione S-transferase, and heavy metal-associated isoprenylated plant protein ( Wu et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Prior research suggests many post-attachment resistance reactions against parasitic plants leverage inducible mechanisms that precisely activate in the presence of such parasites ( Jhu et al, 2022a ). This intricate host-parasitic plant interplay likely guides the co-evolution of resistance strategies, explaining the diverse gene expression profiles and resistance responses among different crop genotypes cultivated across various African regions ( Kavuluko et al, 2021 ; Mutinda et al, 2023 ). Embracing inducible defence responses holds critical significance in genetic engineering and breeding endeavours geared towards developing improved future crops ( Gurr and Rushton, 2005 ).…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…Mutinda et al investigated five sorghum genotypes with documented Striga post-attachment resistance phenotypes ( Kavuluko et al , 2021 ) and revealed genotype-specific gene expression signatures underlying two major resistance mechanisms. Biological processes enriched within these molecular signatures were used to classify responses to Striga into pattern-triggered immunity (PTI) and effector-triggered immunity (ETI) in these five cultivars ( Mutinda et al , 2023 ).…”
Section: Unveiling Modes and Mechanisms Of Post-attachment Resistancementioning
confidence: 99%
“…Current agricultural practices are insufficient to manage Striga infestation, necessitating sustainable approaches that harness natural resistance mechanisms. Mutinda et al (2023) examined how different genotypes of sorghum plants resist Striga after it attacks their roots. By comparing transcriptomes, they found that sorghum activates its immune system, and molecular signatures probably associate with distinct resistance mechanisms.…”
mentioning
confidence: 99%